Review and analysis of the pollution impacts form Vietnamese manufacturing sectors (The World Bank, 2008)
This report was original initiated under the concept of a country envionmental analysis for Vietnam with Vietnamese counterparts. It was decided to limit the focus of the report to trends in industrial development. The report comprises 5 sections: Sec.1 an overview of the industrial sector and projected economic relavance; sec.2 analysis of popullation structure and impacts ; sec.3 review and analysis of environmental protection expenditure for the industrial sector ; sec.4-5 indintify areas where the Government could focus its efforts.